PERILAKU KECURANGAN AKADEMIK MAHASISWA AKUNTANSI: DIMENSI FRAUD DIAMOND SERTA DAYA SAING - Mila Ulpa; Rd. Ade Tribuana Anjaya (Universitas Muara Bungo, 2022)
Education is a way to educate the nation, and educational goals will not be realized if there is still academic fraud. Based on the results of initial observations, there is academic fraud in accounting students. This study aims to determine knowledge of pressure, opportunity, rationalization, ability, and competitiveness partially or simultaneously among Muara Bungo University accounting students. This research method is quantitative, with the population being UMB Accounting students. The research sample was 99 students with data collection using a questionnaire. The data analysis technique is multiple linear regression. The results of the partial test show that only competitiveness influences fraud behavior, while simultaneously all variables influence fraud behavior. The contribution of pressure, opportunity, rationalization, ability, and competitiveness can affect academic fraud by 24.3% while 75.7% is influenced by other variables that have not been in this study. Hopefully this research can become one of the pieces of information in making decisions on academic cheating.